Beating Burnout, Finding Balance Mindful Lessons for a Meaningful Life. - Calarco, Melo (John Wiley & Sons, Incorporated, 2023)
Manage overwhelm and find renewed passion in your life and work Never-ending to-do lists, constant deadlines, intense workloads and the guilty feeling you're not doing enough--does this sound all too familiar? If so, it's time to take a step back and find a better balance for your work and life. In this book, you'll discover the simple practices that will help you create a healthy mindset, boost your wellbeing and prevent overwhelm. So say goodbye to fatigue: with Beating Burnout, Finding Balance, you'll rediscover the energy you need to thrive. Mindfulness and performance coach Melo Calarco shares the secrets to flourishing as a high achiever and an effective leader. In this book, he combines science, practical knowledge and mindfulness techniques with the incredible life lessons he has learned as he cycled and trekked his way around the world. You'll learn how you can apply the strategies that top performers--from surgeons to CEOs to Olympic athletes--use to conquer burnout and surpass their goals. Use simple but highly effective strategies to improve your productivity and happiness Develop your self-awareness so you can better balance your energy Build resilience and manage stress so you can perform in high-stakes or unpredictable situations Find your focus and live with purpose, passion, and drive Through inspirational stories and proven techniques, from mountaintop monasteries to executive boardrooms, Beating Burnout, Finding Balance gives you the tools to achieve your goals and live more meaningfully and mindfully.